Stressors Among Counterterrorism Professionals in Indonesia - Sukabdi, Zora Arfina; Purnama, Chandra Yudistira; Ruliana, Winda; Muzayanah, Umi (Pusat Studi Politik dan Kebijakan Strategis Indonesia (POLKASI), 2025)
Counterterrorism professionals in Indonesia face significant pressures due to the demanding nature of their work. This study was aimed at investigating stressors among Indonesian counterterrorism personnel. A mixed-methods research design was employed in the study. The results demonstrate that counterterrorism professionals, including national intelligence operatives, encounter stress chiefly from role expectations, workload, and insufficient social support. Different demographic groups view certain stressors as the most challenging. Furthermore, statistical evidence indicates that employment in security and national defence, or broader intelligence sectors significantly affects personnel's occupational stress levels. The study may help in developing resilience capacity-building strategies.